TATA KELOLA VERIFIKASI PARTAI POLITIK PESERTA PEMILIHAN UMUM TAHUN 2019 DI KOMISI PEMILIHAN UMUM KOTA PADANG - Indra Madan Putra; Ria Ariany; Syahrizal Syahrizal (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This study aims to show how electoral governance in verification and the efforts of political parties is carried out by the General Election Commission of the City of Padang. One part of the stages of organizing elections is verification. Verification is a very important stage, considering that at this stage political parties are determined to be participants of the 2019 election. The governance of elections in the registration and verification of political parties by the General Election Commission of Padang City as the election organizer has done its job in verifying political parties, but still far from ideal, both at the level of rule-making and application level. However, at the level of adjudication, the General Election Commission of Padang City has seen several steps taken. The efforts made by the General Election Commission of the City of Padang are the dissemination and technical guidance on regulations regarding the registration process and verification of electoral political parties and making a political party verification assistance desk.